Evidence-based orthopedics - Bhandari, Mohit; Adili, Anthony (Evidence-based medicine., 2011)
Surgical orthopedic procedures such as hip replacements, arthroscopy or knee replacements are surrounded by pre- and post-operative complications, and there are varying different methods for the procedures themselves. This book, for the first time, brings together the best evidence for treatments as well as any complications. Not only does it cover the evidence base for orthopedic surgery, but also orthopedic conditions requiring medical treatment, and pediatric orthopedics. Using the approved EBM methodology, and edited by teachers of evidence-based medicine, this is a genuine EBM textbook for all orthopedic specialists and trainees.